Recession Experiences during Early Adulthood Shape Prosocial Attitudes Later in Life - Jan Bietenbeck; Uwe Sunde; Petra Thiemann (Institute of Labor Economics (IZA), 2023)
This paper explores whether the experience of a severe recession during early adulthood shapes individuals' prosocial attitudes. The analysis uses survey responses to experimentally validated questions that measure prosocial attitudes for approximately 65,000 respondents in 75 countries. The identification approach exploits variation in recession experiences across 78 different birth cohorts. We find that exposure to a recession during early adulthood is associated with lower levels of prosociality later in life. The effect only emerges for experiences during impressionable years (age 18–25), mainly affects prosocial attitudes among men, and is orthogonal to the effect of experiences with democracy.
Keywords: D91; E30; E71; 330; prosocial attitudes; impressionable years; experience effects; cohort effects